Morphological design strategies for the renewal of Jiangnan vernacular buildings under the concept of sharing - Li Ningcongying (Lodz University of Technology Press, 2023)
The rapid development of cities has caused a huge siphoning effect on the rural population, resulting in the emergence of ‘hollow villages’ and ‘thousand villages one side’, among other rural problems. In 2017, the 19th National Congress proposed the ‘Rural Revitalization Strategy’ which pushed the study of regeneration and revitalization of vernacular architecture to a new stage, resulting in more and more architects began to enter rural practice. Faced with the current situation of resource constraint, ‘sharing’ provides a new solution for how to revitalize the stock of land, unify urban and rural development and rural revitalization. Through the typological analysis of the transformation process, methods and spatial forms of 7 Jiangnan vernacular cases, such as Stray Birds Art Hotel·Songyang Chenjiapu, Hotel of Septuor, and Culture Neighborhood·Songyang Three-Temple Cultural Communication Centre, etc. five morphological design strategies for the renewal of sharing spaces in vernacular buildings are summarized: space insertion and wrap, space juxtaposition, linear extension, space penetration and visual penetration. Under the premise of respecting the original texture and local culture of the countryside, through the reintegration of old and new spaces, the sharing of functions and spaces can be achieved which can be used as a sharing place and a sharing platform to increase the interaction between users, residents and villagers, thus activating the vitality of the whole region and the countryside and realizing the regeneration and revitalization of the countryside.
Keywords: space insertion & wrap; space juxtaposition; linear extension; space penetration; visual penetration; wstawianie i zawijanie przestrzeni; zestawienie przestrzeni; wydłużanie liniowe; przenikanie przestrzeni; przenikanie wizualne